Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/cryst10100878
|View full text |Cite
|
Sign up to set email alerts
|

Nematogenic Laterally Substituted Supramolecular H-Bonded Complexes Based on Flexible Core

Abstract: New laterally CH3-substituted series of 1:2 hydrogen-bonded supramolecular complexes (HBSMCs) based on flexible acid core were prepared and mesomorphically investigated. Mixtures were formed through H-bonded interactions between adipic acid (A) and 4-(2-(pyridin-4-yl)diazenyl-(3-methylphenyl) 4-alkoxybenzoate (Bn). Mesomorphic and optical properties were investigated by differential scanning calorimetry (DSC), polarized optical microscopy (POM), X-ray diffraction (XRD), and UV-spectroscopy. HBSMCs formed from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…It was found that the insertion of a lateral group on the aromatic ring of the mesogenic part influenced the mesophasic transition temperature range of the smectic phases [ 22 , 23 , 24 ] and increased spontaneous polarization [ 25 ]. The existence of mesophases near room temperature is very important for potential applications; consequently, lateral moieties are incorporated into the molecular architecture to lower the melting temperature [ 26 ]. On the other hand, polar terminal substituents and linking moieties were both important factors for the designed compounds, in terms of the formation, kind, thermal stability, and range of the observed mesophase [ 5 , 12 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the insertion of a lateral group on the aromatic ring of the mesogenic part influenced the mesophasic transition temperature range of the smectic phases [ 22 , 23 , 24 ] and increased spontaneous polarization [ 25 ]. The existence of mesophases near room temperature is very important for potential applications; consequently, lateral moieties are incorporated into the molecular architecture to lower the melting temperature [ 26 ]. On the other hand, polar terminal substituents and linking moieties were both important factors for the designed compounds, in terms of the formation, kind, thermal stability, and range of the observed mesophase [ 5 , 12 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the kind of the symmetrical and unsymmetrical terminal substituents will affect the mesomorphic phenomena [30][31][32][33]. Thus, when a change of the length of the terminal alkyl/alkoxy chains is affected and the rigidity of the structural molecular core is altered, the linearity of the molecules will be accordingly changed, to some extent, due to the higher number of the chain configurations that lead to different interactions between linear molecules [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The small volume of the lateral group enables its additions into the mesomorphic architectures without being sterically disrupted, and consequently, its LC mesophases can still be observed. It has also been documented that lateral or terminal polar substituent induces an effect on the mesomeric properties of huge numbers of Schiff bases/ester derivatives [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%